Isu Tren Penggunaan Teknologi dalam Bahasa Inggris Konteks Pengajaran Bahasa Asing - Dea Aisyah Wulandari; Vopy Ulitia Putry; Fristy Nur Rahmadani; Erwin Pohan (CV. Kalimasada Group Profesional, 2024)
This paper aims to provide a comprehensive understanding of how the use of technology has changed and influenced the way language is learned, and the integration of technology, specifically AI-powered tools like Deep-L QuillBot and Grammarly, impacted foreign language teaching and learning. This study through narrative reviews, researchers can combine several viewpoints and utilize the distinct perspectives of the review team, which will influence the analysis. The integration of artificial intelligence-based technologies such as Deep-L, Grammarly, and QuillBot has proven to be instrumental in enhancing foreign language learning, particularly in improving students'' writing skills. Studies show a trend in recent years of using AI tools Deep-L, Grammarly and QuillBot of measurable improvements in language skills, such as better understanding of sentence structure and reduced grammatical errors.